Progress in animal models for studying hyperuricemia - Zhang, Senyue; Li, Kaiqing; Zhang, Hu; Fu, Tong; Ma, Yanchun; Zhang, Shuxiang; Xing, Guoli; Tong, Ying (Frontiers in Pharmacology, 2025)
Hyperuricemia (HUA) is a prevalent metabolic disorder driven by dysregulated purine metabolism and impaired urate excretion, and robust animal models are critical for elucidating its pathophysiology and guiding therapy development. This review systematically examines chemically induced, gene‐edited, environmental, exercise and microbiota‐based HUA models across rodents, poultry, primates, zebrafish and silkworms, highlighting each model’s strengths and limitations in mimicking human uric acid handling. We discuss how these models have validated standard urate‐lowering treatments—such as xanthine oxidase inhibitors and uricosurics—and uncovered emerging therapeutic targets, including the gut–NLRP3 inflammasome axis and SIRT1‐mediated ABCG2 regulation. Finally, we propose a unified three‐tier framework encompassing biochemical, mechanistic and pathological criteria to standardize model evaluation and accelerate translational research in hyperuricemia.